A tumor-targeted polymer theranostics platform for positron emission tomography and fluorescence imaging - Koziolová, Eva; Goel, Shreya; Chytil, Petr; Janoušková, Olga; Barnhart, Todd E; Cai, Weibo; Etrych, Tomáš (Nanoscale, 2017)
Here, we describe a novel polymer platform suitable for efficient diagnostics and potential theranostics based on 89Zr-labeled N-(2-hydroxypropyl)methacrylamide (HPMA)-based copolymer conjugates. A set of polymers differing in molecular weight with either low dispersity or high dispersity were designed and synthesized and their biodistribution in vivo was successfully and precisely observed over 72 h. Moreover, the feasibility of two imaging techniques, fluorescence imaging (FI) and positron emission tomography (PET), was compared using labeled polymer conjugates. Both methods gave comparable results thus showing the enhanced diagnostic potential of the prepared polymer-dye or polymer-chelator-89Zr constructs. The in vivo and ex vivo PET/FI studies indicated that the dispersity and molecular weight of the linear HPMA polymers have a significant influence on the pharmacokinetics of the polymer conjugates. The higher molecular weight and narrower distribution of molecular weights of the polymer carriers improve their pharmacokinetic profile for highly prolonged blood circulation and enhanced tumor uptake. Moreover, the same polymer carrier with the anticancer drug doxorubicin bound by a pH-sensitive hydrazone bond showed higher cytotoxicity and cellular uptake in vitro. Therefore, HPMA copolymers with low dispersity and a molecular weight near the limit of renal filtration can be used as highly efficient polymer carriers of tumor-targeted therapeutics or for theranostics with minimal side effects.
Keywords: Jurkat Cells; radionuklidy; tkáňová distribuce; doxorubicin; Cell Line, Tumor; Tissue Distribution; optické zobrazování; Jurkat buňky; Positron-Emission Tomography; pozitronová emisní tomografie; myši inbrední BALB C; Neoplasms, Experimental; Drug Carriers; Polymers; Mice, Inbred BALB C; MFC-7 buňky; Theranostic Nanomedicine; Zirconium; MCF-7 Cells; Animals; lidé; experimentální nádory; ženské pohlaví; polymery; Humans; Optical Imaging; zvířata; Radioisotopes; myši; zirkonium; teranostická nanomedicína; nádorové buněčné linie; Mice; Female; nosiče léků; Doxorubicin